Breve reflexão sobre o património artístico da Faculdade de Medicina da Universidade de Lisboa - Ana Mehnert Pascoal (Midas: Museus e Estudos Interdisciplinares)
The artistic heritage of the Faculty of Medicine of the University of Lisbon has its origins in the Escola Médico-Cirúrgica de Lisboa (1836-1911). It includes paintings and sculptures, mostly authored by nationally renowned artists such as José Malhoa, Columbano Bordalo Pinheiro or Simões de Almeida. The present article intends to characterize and examine this heritage through the angle of institutional history and memory in the context of a scientific institution. A brief analysis on the importance of this typology of university heritage is followed by the discussion of management, preservation and dissemination issues, illustrated with national and international examples.